Religiusitas dan Kesejahteraan Psikologis Mahasiswa Fakultas Dakwah - Beti Malia Rahma Hidayati; Tika Nur Fadhilah (Universitas Islam Tribakti Lirboyo Kediri, 2021)
This study reveals the level of religiosity and psychological well-being of students at the Da'wah Faculty of IAIT Kediri. It describes the influence of religiosity on psychological well-being in the same students. The distribution of the religiosity questionnaire was based on Glock and Stak's theory, while the distribution of the psychological well-being questionnaire was based on Ryff's theory. The sample of this research is the population itself, considering the total population is less than 100. The data is processed using a simple linear regression formula. The result shows that the students' religiosity of the Da'wah Faculty of IAIT Kediri has a significant effect on psychological well-being.